Assessing Financial Synergies through DuPont Analysis and Economic Value Added in the Post-Acquisition Integration of PT Petronesia Benimel - Bhaskoro Perwiro Utomo; Maria Ulpah (Green Publisher Indonesia, 2025)
Strategic mergers and acquisitions (M&A) have an important role for companies in emerging markets to accelerate growth and improve operational efficiency, especially in the infrastructure sector which is crucial for national development. This study evaluates the financial performance of PT Petronesia Benimel, an Indonesian construction company that is not listed on the stock exchange, before and after its acquisition in 2020 by PT Hutama Karya Infrastruktur, a state-owned enterprise responsible for the Trans-Sumatra Toll Road project. Using a mixed-methods approach, this study integrates DuPont and Economic Value Added analysis to assess profitability, operational efficiency, and shareholder value creation, reinforced by qualitative insights from managerial interviews. Quantitative analysis of financial data before (2015–2019) and after the acquisition (2020–2024) showed a significant decrease in Return on Equity (ROE) from 18.7% to 5.5% (p = 0.025), due to a decrease in net profit margin and asset utilization efficiency. Economic Value Added (EVA) also showed a substantial decrease from positive IDR 5,041 million to negative IDR -20,455 million, with a statistically insignificant decrease (p = 0.095), reflecting the company's inability to generate returns that exceed the cost of capital. The qualitative findings reinforce these results, by attributing the decline in financial performance to the inefficiencies of the integration process, the increased debt burden, as well as the external impact of the COVID-19 pandemic, such as project delays, liquidity pressures, and increased operational costs.